Наноструктурированные пленки ZnO для устройств микроэлектроники и оптики - Belyanin, A. F.; Krivchenko, V. A.; Lopaev, D. V.; Pavlushkin, L. V.; Paschenko, P. V.; Pirogov, V. G.; Polyakov, S. N.; Suetin, N. V.; Sushentsov, N. I.; Suetin, N. V. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
ZnO films were obtained by RF magnetron sputtering. An additional magnetic field was applied using a magnetic system placed behind the substrate holder. The influence of process parameters on the structure and functional properties of the films was established. ZnO films were employed in the development of surface acoustic wave filters and ultraviolet mirrors